Management of ICT-Based Blended Learning of Grammar atEnglish Department of Universitas Muhammadiyah Parepare (A Micro-Ethnography Study) - Badaruddin, Badaruddin; , Prof. Dr. Budi Murtiyasa, M.Kom; , Prof. Dr. Endang Fauziati, M. Hum (2013)
The development of Information Communication and Technology providing a lot of facilities has brought a new change and paradigm in distance learning, above all blended learning. Its rapid and quick development has encouraged some teachers and researchers to carry out blended learning in their teaching and research. One of them is the implementation of blended learning carried out in English Department of Universitas Muhammadiyah Parepare. The main purpose of this study is to describe the management of ICT-based blended learning of grammar at English Department of Universitas Muhammadiyah Parepare. This major objective consists of threefold, namely 1) it is aimed to describe the planning of ICT-based blended learning of grammar including the organization of material, the selection of media and the selection of method, 2) to describe its implementation including the organization of learning activities, the management of learning environment, the directing of student activity and the controlling of student achievement, and 3) to describe its evaluation including standard of assessment used and model of evaluation used. This study is a qualitative research with an ethnography approach. The subject of this research consists of one grammar teacher, one teacher assistant, and ten grammar students of fifth semester of English Department of Universitas Muhammadiyah Parepare. In collecting data, it employs participative observation, in-depth interview and documentation. The result shows that the first, planning of ICT-based blended learning including material taught, media used and method chosen is planned and managed maturely based on what content of material taught, student needs and what the learning objective or competence to be achieved. Second, the implementation of ICT-based blended learning of grammar. The result describes that the implementation of ICT-based blended learning of grammar can create an interesting, effective and efficient learning environment so it can build the student's learning interest and motivate the student to learn independently. Finally, it is evaluation phase. The result indicates that the teacher uses two kinds of assessment standard, namely criterion-referenced and normative-referenced assessment. Meanwhile, in evaluation the student achievement and performance the teacher refers to Kirkpatricks's 4 level models.